Tren Epidemiologi Global Antimicrobial Resistance (AMR) sebagai Ancaman Kesehatan Masyarakat Strategis - Angela Ade Febrianza; Indah Maulidya Sari; Fadhila Kurnia Putri; Alfianti Suci Nurmalasari (Pelantar Press, 2026)
Antimicrobial resistance (AMR) has emerged as one of the major global public health threats that reduces the effectiveness of antibiotic therapy and increases the burden of infectious diseases worldwide. This study aimed to review the global epidemiological trends of antimicrobial resistance based on distribution patterns, determinants, public health impacts, and challenges in controlling AMR. This study used a descriptive narrative literature review approach by analyzing scientific publications published between 2015 and 2025 obtained from international databases including PubMed, ScienceDirect, Google Scholar, and WHO reports. The findings showed that the global burden of antimicrobial resistance continues to increase and is influenced by irrational antibiotic use, limited surveillance systems, and gaps in the implementation of antimicrobial stewardship programs across countries. AMR contributes to increased mortality, prolonged hospitalization, higher healthcare costs, and threatens the effectiveness of modern medical procedures. In addition, the emergence of priority resistant pathogens and the limited availability of new antibiotics further strengthen the urgency of integrated control strategies. Strengthening surveillance systems, promoting rational antibiotic use, and implementing a multisectoral One Health approach are essential to reduce the global impact of antimicrobial resistance